2019
DOI: 10.1021/acsanm.9b01438
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate Immobilized on Graphene via Click Reaction for Simultaneous Dismutation of H2O2 and Oxidation of Sulfur Mustard Simulant

Abstract: Click reactions" are widely used for the synthesis and modification of new materials due to their fascinating advantages (e.g., highly efficient and selective, mild reaction conditions, and lack of side reactions). Redox-active metal-substituted polyoxotungstates (MSPs) were covalently immobilized on a graphene surface by using a "click" reaction between the azido group of K 1.5 Cs 5.5 [γ-SiW 10 O 39 Cu 2 (N 3 ) 2 ] (SiW 10 Cu 2 (N 3 ) 2 ) and the alkynyl groups on functionalized graphene. This novel strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Remarkably, the catalytic oxidation activity of 1 toward CEES is comparable to those of the reported POM-based metal–organic catalysts. For example, the conversion of CEES catalyzed by 1 is up to 99% with a CEESO selectivity of 97% at 40 °C within 25 min (entry 2, Table ). For the known PW 12 @NU-1000 catalyst, a similar conversion (98%) of CEES was achieved under the similar conditions, but the selectivity of CEESO is only up to 57% .…”
Section: Resultsmentioning
confidence: 57%
“…Remarkably, the catalytic oxidation activity of 1 toward CEES is comparable to those of the reported POM-based metal–organic catalysts. For example, the conversion of CEES catalyzed by 1 is up to 99% with a CEESO selectivity of 97% at 40 °C within 25 min (entry 2, Table ). For the known PW 12 @NU-1000 catalyst, a similar conversion (98%) of CEES was achieved under the similar conditions, but the selectivity of CEESO is only up to 57% .…”
Section: Resultsmentioning
confidence: 57%
“…The pressure drop without AFP in the xture is 137.2 Pa. The permeability coefficient (K f , %) was calculated using formula (4) and the ltration efficiency (h, %) was calculated using formula (5). The pressure drop of the AFP was measured using an inclined micromanometer.…”
Section: General Performance Test Of Sd-afpmentioning
confidence: 99%
“…3,4 It not only poses a threat to personnel and equipment, but also makes it more difficult to dispose of scrap. In recent years, the integrated technology for protection and decontamination has continued to develop, and a number of protective materials, such as carbon 5 and polymer materials, [6][7][8] with self-decontamination function have been exploited one aer another. For example, John Walker et al 9 added organic phosphate dehydratase OPAA and modied dehydratase OPAA-C18 coated with high-branched polyvinyloxazoline into the spinning dope and adopted a highvoltage electrostatic ber-forming process to obtain a selfdetoxifying membrane, which can effectively promote the hydrolysis of the chemical warfare agents (CWAs) simulant diisopropyluorophosphate (DIFP).…”
Section: Introductionmentioning
confidence: 99%
“…[90][91][92][93] It is worth mentioning that the nature of the metal ions in each of the binary catalyst series have little impact on the reaction rates.P OMs immobilized on solid supports have also been studied for the catalysis of CEES oxidation to CEESO by H 2 O 2 .T hese heterogeneous systemsi nclude ar eticulatedg el materiali ncorporating hexavanadate clusters (entry 6), [94] am ixed Zn/Cr hydroxide layer materialw ith intercalated transition metal-substituted polyoxotungstate (entry 7), [95] and aC u-substituted POM [Si-W 10 O 36 Cu 2 (N 3 ) 2 ] 6À that was bondedt ot he surfaceo fg raphene by an alkyne-azidec ycloaddition( entry 8);t his was also studied as ac atalystf or CEES oxidationb yO 2 (see section 3.4.2). [96] Overall,m any POMs efficiently catalyze the oxidation of CEES by H 2 O 2 ,b ut the gain (in catalytic rates) compared with simple monomeric anionic metal oxidesi sr ather limited.…”
Section: Poms As Oxidation Catalysts With Peroxidesmentioning
confidence: 99%
“…[61] Wang and co-workers reported that graphene-immobilized [SiW 10 O 36 Cu 2 (N 3 ) 2 ] 6À (section 3.4.1) catalyzed the selective oxidation of CEES to sulfoxide under af low of dioxygen (10 mL min À1 )i n7 5% yield over 6h.T he conversion is approximately six times slower compared with the same process in-volvingH 2 O 2 insteado fO 2 as the oxidant. [96] 4. Photocatalytic Neutralization…”
Section: Poms As Oxidation Catalysts With Dioxygenmentioning
confidence: 99%